No More Homework? Negotiations of Parental Engagement in All-Day Schools - Schuler Braunschweig, Patricia; Kappler, Christa; Chiapparini, Emanuela (International Journal about Parents in Education, 2023)
In the course of the implementation of all-day schools in Zurich, traditional homework has been integrated within the new educational system. This action is altering the arrangement and opportunity of parental engagement and requires new negotiation processes between family and school. In this qualitative study including interviews with parents (n=8), three patterns of relational connection between parents and professionals were found. The integration of homework is perceived either as a relief or as a loss of control and requests an adaption of communicative forms. It can be seen that parental engagement in children’s learning at home highly depends on individual parents’ attitudes and trust toward school as well as the student’s success at school.